PENYELESAIN TERHADAP PELAKU TINDAK PIDANA ZINA MELALUI MEDIASI PENAL BERDASARKAN HUKUM ADAT MELAYU RIAU DI KABUPATEN SIAK - Epraim Ketaren; Evi Deliana; Erdiansyah Erdiansyah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
The application of customary law which is criminal in the form of sanctions in the form of fines, sanctions being expelled from the village, sanctions and being excluded from social interactions. Especially in the customary crime in Siak Regency, in this case regarding the settlement of the perpetrator of the crime of adultery through penal mediation in the area because the people in the area still maintain and still maintain the existence of Malay customary law in the Siak Regency area. Then the settlement of the criminal act of adultery through penal mediation based on Riau Malay customary law in Siak Regency is recognized. The objectives of this thesis are: First, to find out the settlement process for adultery perpetrators through penal mediation based on Riau Malay Customary law in Siak Regency. Second, to find out the view of criminal law as positive law on the settlement of criminal acts of adultery which are resolved under the Riau Malay Customary law in Siak Regency.This type of research can be classified as a type of sociological legal research, because in this study the author directly conducts research at the location or places that are studied to provide a complete and clear picture of the problem under study. This research was conducted at the Riau Malay Customary Institution located in Siak Regency, while the population and sample were all parts related to this research. interviews and literature studies.From the results of the research and discussion it can be concluded that, first, the settlement process of the criminal fornication through penal mediation based on Riau Malay Customary law in Siak Regency is still recognized for its existence and the process consists of the preparation stage, the settlement process, the decision from the settlement process and the implementation of the . Second, the View of Criminal Law as Positive Law on the Settlement of Criminal Acts of Adultery Resolved by Riau Malay Customary Law in Siak Regency, namely: recognition of values that live in society in a modern legal system, application of penal mediation which is later legalized by the state justice system and apply penal meditation (settlement) according to society without any state interference.Keywords: Settlement - Law - Adat - Penal Mediation - Adultery